Changes in the leukocyte component and the role of hematological indices in cardiovascular diseases: focus on surgical myocardial revascularization (literature review) - M. A. Kuzmichkina; V. S. Kaveshnikov (Российский кардиологический журнал, 2024)
The high prevalence of cardiovascular diseases inevitably entails an increase in the number of annual surgical myocardial revascularization procedures. In this regard, the increasing risk of postoperative complications is obvious. The aim of this work was to analyze the available literature on the study of the systemic inflammatory response (SIR) in cardiovascular diseases with an emphasis on coronary artery bypass grafting (CABG). The study of the mechanisms of SIR after cardiac surgery allowed attempts to suppress the activity of the cytokinin storm. The main significance of leukocytes in the initiation of SIR served as the reason for studying the prognostic value of the leukocyte level, both in the postoperative and preoperative periods. The article reflects data on the role of hematological markers and indices. In addition, the results of studies on the significance of a normal high level of leukocytes in the preoperative period are presented, since a negative prognosis was noted in such a group of people who underwent CABG. While remaining a widely accessible and inexpensive method, the assessment of the leukocyte formula, as well as the calculated hematological indices, acquire predictive value for postoperative complications and outcomes.